Analyzing the Impact of Integrated Marketing Strategies on Consumer Behavior and Brand Equity in Competitive Market (Architecture Image Studies, 2026)
The integration of marketing strategies has become a determinant of business success in a competitive and digitally-driven business environment, which affects consumer behaviour and brand equity. In this paper, the intricate impacts of IMS on the key consumer behavioural outcomes, including satisfaction, loyalty, service delivery, online interaction and brand communication, are considered in relation to the purchase intention, likelihood of recommendation, and satisfaction. The study relies on descriptive statistics, correlation, and regression analysis in Microsoft Excel and Google sheets to examine the multifaceted relationships among marketing factors, consumer response, and brand performance measurements based on a synthetic dataset developed on the basis of publicly available Kaggle sources. The findings indicate that customer satisfaction, trust, and recommendation intentions have been identified to be the key mediators between IMS and augmented brand awareness, perceived quality, loyalty and long-term equity. Psychological and emotional factors such as self-esteem, involvement and engagement depict significant contribution in triggering purchasing pronouncements and advocacy behaviours. The research builds on the existing literature by offering a broad data-based reflection of the role of integrated and customer-focused marketing strategies in developing sustainable competitive advantage. Practical implications are provided to practitioners who want to create consistent and effective marketing programs that can stimulate consumer interest, reinforce brand positioning, and facilitate long-term business development in the dynamic market settings.